Complexation Studies of Zn2+, Cu2+, Co2+, Ni2+ and Cd2+ Ions with a Schiff Base Ligand - Payehghadr, Mahmood (Orbital: The Electronic Journal of Chemistry, 2017)
The complex-formation reactions between Zn2+, Cu2+, Co2+, Ni2+ and Cd2+ ions with, N,N’–Bis-(salicylidene)1,8-diamino-3,6-dioxaoctan Schiff base ligand, has been studied by spectrophotometric method in acetonitrile at various temperatures. The formation constant (Kf) and the molar absorptivity (ε) of the resulting complexes between ligand and different cations were calculated by fitting the observed absorbance at various [M2+]/[L] mole ratios and found that the stability of the resulting L-M2+ complexes varied in the order Cu2+ > Zn2+ > Co2+ > Ni2+ > Cd2+. The enthalpy and entropy changes of the complexation reaction were determined from the temperature dependence of the formation constants. DOI: http://dx.doi.org/10.17807/orbital.v9i4.1014